Spread and Control of Mobile Benign Worm Based on Two-Stage Repairing Mechanism - Meng Wang; Zhide Chen; Li Xu; Huan Zhan (Journal of Applied Mathematics)
Both in traditional social network and in mobile network environment, the worm is a serious threat, and this threat is growing all the time. Mobile smartphones generally promote the development of mobile network. The traditional antivirus technologies have become powerless when facing mobile networks. The development of benign worms, especially active benign worms and passive benign worms, has become a new network security measure. In this paper, we focused on the spread of worm in mobile environment and proposed the benign worm control and repair mechanism. The control process of mobile benign worms is divided into two stages: the first stage is rapid repair control, which uses active benign worm to deal with malicious worm in the mobile network; when the network is relatively stable, it enters the second stage of postrepair and uses passive mode to optimize the environment for the purpose of controlling the mobile network. Considering whether the existence of benign worm, we simplified the model and analyzed the four situations. Finally, we use simulation to verify the model. This control mechanism for benign worm propagation is of guiding significance to control the network security.